A cross sectional study on breast feeding practices among mothers in the urban slums of greater Hyderabad, Telangana - Mummadi, Mahesh Kumar; Kusneniwar, Govind N. (International Journal of Contemporary Pediatrics, 2017)
Background: Breastfeeding is the normal way of providing young infants with the nutrients they need for healthy growth and development. After delivery, routine newborn care procedures that separate mother and baby should be delayed for at least the first hour to allow mother and newborn to be in uninterrupted skin-to-skin contact to encourage and promote initiation of breastfeeding within the first hour. National Family Health Survey (NFHS)-4 shows children under 3 years breastfed within one hour of birth was 40.1%. Most of the studies on breast feeding practices including NFHS -4 are limited to either urban or rural but not in urban slums. Hence, present study was conducted especially in urban slums of Greater Hyderabad, Telangana. Methods: A cross sectional study was conducted during May to October 2013 in the urban slums of Hyderabad Outskirts. Out of four slums two were randomly selected for the study. The questionnaire was adapted from Action against hunger (ACF-USA) and modified to suit the study. Information was collected by house to house visit and questionnaire was administered to the mothers who had children less than 3 years of age. Data was entered in MS Excel and analysed using Epi info 7. Results: A total of 112 mothers participated in the study. Of them 97.3% breast fed their children and 2.7% did not. Breast feeding was initiated within an hour among 50.89%. Pre-lacteal feeds given in 23.21%. Of them 34.6% gave buffalo milk, 30.8% gave honey, 19.2% gave sugar water and 15.4% gave infant formula. 83.03% received breast milk within 24 hrs. 54% practiced Exclusive breastfeeding. 33.1% reported having used bottle feeding, 10.7% reported having used a pacifier, of them 19.2% had low milk secretion, 3.85% were busy, 61.54% used it to stop the baby crying. Conclusions: Breast feeding practices were adequate with initiation within one hour was fine which needs to be increased by promoting importance of breast feeding. Practice of pre- lacteal feeds was high. There is a marked difference between exclusively breastfed percentage in different parts of India.